Reality of job burnout among the employees of the National Bank of Saudi Arabia in KSA - Al-Zahrani, Mariam Abdullah (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to reveal the reality of job burnout among the employees of the National Bank of Saudi Arabia, by revealing the reality of emotional stress, reality of the feeling of low personal achievement at work, reality of the negative attitude towards self and others among the employees of the National Bank in the Kingdom of Saudi Arabia. To achieve this goal, the study used the descriptive analytical method, and the questionnaire as a tool for collecting data from the study sample, and the study population represented all employees in the collection department in the branches of the National Bank in the Kingdom of Saudi Arabia. The study found that the level of emotional stress among the employees of the collection department at the National Bank of Saudi Arabia was (large) and mean (3.547), and the level of feeling low personal achievement at work was (weak) and mean (2.575), and the level of negative attitude towards Self and others with a degree (medium) and an mean of (2.731). The study recommends the importance of evaluating the work environment in the collection department and working to improve it to the best possible extent. Paying attention to programs to develop the capabilities and skills of employees, provided that they are part of the official working days. In addition, the development of the incentive system by focusing on diversifying incentives between material and moral.